2008
DOI: 10.1007/s00423-008-0358-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgical work volume on postoperative complication: superiority of specialized center in gastric cancer treatment

Abstract: Purpose We investigated the risk factors for early postoperative complications after gastric cancer surgery. Materials and methods The data from a total of 273 patients with gastric cancer were analyzed by univariate and multivariate analysis. We applied physiological and operative severity score for the enumeration of morbidity and mortality (POSSUM) to compare risk-adjusted surgical outcomes among different surgical units. Results Among the preoperative variables, patient gender, chronic obstructive pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 19 publications
5
22
2
1
Order By: Relevance
“…Several studies suggested that GC surgery should be performed in specialized centers as they found the rate of mortality and morbidity was significantly lower if GC patients were operated on by surgeons with high caseloads or coming from specialized units [15][16][17]. Our result was different from these studies.…”
Section: Discussioncontrasting
confidence: 96%
“…Several studies suggested that GC surgery should be performed in specialized centers as they found the rate of mortality and morbidity was significantly lower if GC patients were operated on by surgeons with high caseloads or coming from specialized units [15][16][17]. Our result was different from these studies.…”
Section: Discussioncontrasting
confidence: 96%
“…This finding is consistent with study conducted by Kumar et al [31] in which intraoperative blood loss showed significant association with postoperative pulmonary complications. The possible explanation for this could be because of increased risk of transfusion which decreases immunity.…”
Section: Discussionsupporting
confidence: 93%
“…This is also consistent with study conducted by Daniel et al [30] where use of epidural analgesia has brought significant reduction in postoperative pneumonia as compared to those patients who were not given epidural analgesia in patients undergoing thoracic and abdominal surgeries [31]. This could be explained by impairment of effective breathing and coughing reflexes due to pain especially in procedures done on upper abdomen and intra thorax, thereby leading to hypoventilation and sputum retention; which intern lead to postoperative pulmonary complications as hypoxia, atelectasis and pneumonia.…”
Section: Discussionsupporting
confidence: 91%
“…We found a positive relationship between higher hospital volume and both lower morbidity in JCOG9501 and reduced blood loss in [29]. Two other studies also showed a positive relationship between surgeon volume and shortterm outcomes [30,31]. Our study showed nonstatistically significant correlations between surgeon volume and the number of dissected lymph nodes and blood loss volume.…”
Section: Discussionsupporting
confidence: 66%